Application of Augmented and Virtual Reality Technologies in Medicine - Mohammad Hossein Ronaghi (Tehran University of Medical Sciences, 2021)
Background and Aim: Virtual Reality and Augmented Reality are immersive technologies that integrate virtual and real-world elements. These technologies have been used to help and improve human capabilities in many fields. Virtual and augmented systems are used in various medical situations. They are effective options in most stages of patient treatment and performing medical procedures. Therefore, the purpose of this study is to investigate the applications of virtual and augmented reality technologies in the field of medicine and rank them. Materials and Methods: This applied research was conducted in two phases using mixed-method approach in 2020. Library resources were used in the qualitative phase and a questionnaire in the quantitative phase. The applications of virtual and augmented reality technologies were ranked by a panel of experts having 13 members. Finally, Stepwise Weight Assessment Ratio Analysis(SWARA) method was used to rank the applications of technologies in medicine. Results: The results of SWARA method showed that education (0.252), surgery (0.216), health games (0.188), patient control and diagnosis (0.186), and pharma (0.158) were the most important applications of virtual and augmented reality in medicine. Conclusion: Based on the results of this study, it can be acknowledged that medical education and surgery are the most important applications of augmented and virtual reality technologies in medicine. Therefore, policymakers and hospital managers must use this ranking for the development of virtual and augmented reality technologies in their organization to provide better services to the customers and patients.